Analisis Kandungan Unsur Hara pada Eco-enzyme Menggunakan Jeruk (Citrus sinensis) dan Nenas (Ananas comosus): Analysis of Nutrient Content in Eco-enzyme Using Orange (Citrus sinensis) and Pineapple (Ananas comosus) - Sitompul, Hamela Sari; Maulina, Intan; Situmorang, Idawati (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
Organic waste can be broken down into smaller materials and does not cause odour. There are many types of organic waste that we often encounter in nature. One of the organic wastes that we encounter, especially in rural areas, is oranges and pineapples. The study aimed to determine the nutrients in eco-enzymes from pineapple and orange waste. In eco-enzymes, macronutrients, namely organic carbon, Nitrogen (N), Phosphorus (P), and Potassium (K), play a role. The study results for the nutrient parameters of Eco-enzyme content are 1.74% N, 1.98% C-organic, 77.15 mg / l Ca, and 1522.70 mg / l K with a ph of 6.3. These nutrient components significantly meet the specified standard values. These values will affect plant growth and development. Giving eco-enzymes to plants is thought to affect plant vegetative growth. Orange and pineapple fruits are mixed with a ratio of 3 parts organic matter, 1 part molasses and 10 parts clean water, then fermented for 3 months to become an eco-enzyme solution. Samples of the fermentation results are taken and analysed to determine chemical parameters in ph and TDS using the established testing procedures. The method used is laboratory testing with Spectrophotometry and Absorbance tests. The results of recycling pineapple and orange peel waste into eco-enzymes get results that are by the standards for making eco-enzymes. Making eco-zymes is one way to improve environmental quality with zero waste.